(untitled) (Journal Of Educational and Psychological Researches, 2022)
The aim of this research is to identify the availability of visual thinking skills in the chemistry textbook scheduled for the third intermediate grade for the academic year (2020-2021) in the Republic of Iraq. The study sample consisted of all (85) images contained in the chemistry course for the third intermediate grade, which are (85) form using the curriculum. Analytical descriptive A list of visual thinking skills was prepared, and the unit of form was adopted as a unit of analysis and repetition as a unit of counting, and frequencies and percentages were used for statistical treatment, and validity and reliability were calculated. And using the Holste equation. The following results were reached: The skill of analyzing the visual shape obtained the highest percentage, which is (36%), followed by the skill of recognizing the visual shape (31%), then the skill of linking relationships in the visual form came with (12%), followed by the skill of perception and interpretation of ambiguity by (12%). 10%), then the skill of extracting meanings and the skill of distinguishing the visual shape in percentages (6%) and (5%), respectively, and the results show the discrepancy and imbalance of these skills in the book of chemistry for the third intermediate grade.